Colorimetric technique for monitoring water stress in palm oil seedlings - Raypah, Muna Ezzi; Ahmad Fairuz, Omar; Mohd Faizal, Jamlos (Institute of Physics, 2022)
Prevention of stress in the asymptomatic stage of the plants could result in improved crop management. In this study, the water and light stress of three oil palm seedlings (Elaeis Guineensis) was examined by assessing the leaves' colour using CIELAB colour space. The oil palm seedlings were subjected to water stress for 33 days and then to water and light stress from 55 to 78 day (for 25 days). The variation of the colour of the leaves due to water stress was discussed in detail. The approach used in this study to identify the drought stress may allow for differentiating mild environmental and severe drought stress in oil palm plants and may be used for remote field-scale estimation of plant stress resistance and health.